2014
DOI: 10.1097/brs.0000000000000166
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Increase in Adjacent Discs During Clinical Discography Questions the Methods Validity

Abstract: 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Furthermore, studies have shown that the degenerative process within a disc can be initiated with a mere needle puncture (ie, that performed during lumbar discography) [41][42][43][44][45][46][47][48][49][50]. A recent study has demonstrated pressure increases in adjacent level discs during lumbar discography, which similarly led the authors to the conclusion to question the method's validity [51]. Therefore, discography was not used as a diagnostic tool in the present study.…”
Section: Preoperative Diagnosis and Patient Selectionmentioning
confidence: 86%
“…Furthermore, studies have shown that the degenerative process within a disc can be initiated with a mere needle puncture (ie, that performed during lumbar discography) [41][42][43][44][45][46][47][48][49][50]. A recent study has demonstrated pressure increases in adjacent level discs during lumbar discography, which similarly led the authors to the conclusion to question the method's validity [51]. Therefore, discography was not used as a diagnostic tool in the present study.…”
Section: Preoperative Diagnosis and Patient Selectionmentioning
confidence: 86%
“…This state, discogenic pain, is reported by some to be reliably revealed by concordant pain reaction at discography [17][18][19][20][21], but others are in disagreement [22][23][24]. When using this test procedure Schwarzer et al [19] were unable to differentiate patients with discogenic pain clinically from other patients within the CLBP population.…”
Section: Discussionmentioning
confidence: 96%
“…Logically, provocative discography would be the most suitable test for pinpointing a painful disc, and several reports defend this opinion [17][18][19][20][21][28][29][30][31] while others do not [22][23][24]31,32]. In fusion surgery in patients suffering from non-specific CLBP Madan et al [22] and Carragee et al [23] did not find pain reaction at discography to be a reliable method for pinpointing a presumed painful disc.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that the injected contrast agent in itself may cause accelerated degeneration by inducing cell apoptosis [44]. In addition, it was recently demonstrated that discography-induced pressure increases not only in the injected disc, but also in adjacent discs potentially inducing false-positive responses [8][9][10]. This strongly questions the validity of discography as a tool-provoking pain on a single disc level only.…”
Section: Discussionmentioning
confidence: 97%
“…Discography remains, however, questioned due to factors such as inconclusiveness regarding false-positive responses, lack of ''gold standard'' and uncertainty of what actually causes the pain in or around the disc [3][4][5][6][7]. A recent finding that discography induces a significant pressure increase not only in the injected disc, but also in adjacent discs that further raises new questions about discography's validity [8][9][10].…”
Section: Introductionmentioning
confidence: 98%